Mobile app-based symptom-rhythm correlation assessment in patients with persistent atrial fibrillation. (19th May 2022) - Hermans, ANL; Gawalko, M; Pluymaekers, NAHA; Verhaert, DVM; Van Der Velden, RMJ; Betz, K; Evens, S; Luermans, JGLM; Den Uijl, DW; Baumert, M; Vernooy, K; Rienstra, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: In patients with persistent atrial fibrillation (AF) it is difficult to determine the association between patient self-reported symptoms and the underlying heart rhythm (symptom-rhythm correlation [SRC]). No standardized strategy to assess SRC in AF patients is available. Purpose: We assessed for the first time SRC in persistent AF patients using a mobile health approach of simultaneous photoplethysmography (PPG)-based rhythm monitoring and active interrogation of patient-reported symptoms, which provides a novel approach to systematically assess SRC in persistent AF. Methods: Consecutive persistent AF patients planned for electrical cardioversion (ECV) used a mobile app to record a 60-second PPG and report symptoms once daily and in case of symptoms for four weeks prior and three weeks after ECV. Within each patient, SRC was quantified by the SRC-index defined as the sum of symptomatic AF recordings and asymptomatic non-AF recordings divided by the sum of all recordings. Results: Of 88 patients (33% female, age 68±9 years) included, 78% reported any symptoms during recordings. The overall SRC-index was 0.61 (0.44-0.79). The study population was divided into SRC-index tertiles: low (<0.47), medium (0.47-0.73) and high (≥0.73). Patients within the low (vs high) SRC-index tertile had more often heart failure and diabetes mellitus (both 24.1% vs 6.9%). Extrasystoles occurred in 19% of all symptomatic non-AF PPG recordings. Within each patient, PPG recordings with the highest (vs lowest) tertile of pulse rates conferred an increased risk for symptomatic AF recordings (odds ratio [OR] 1.26, 95% coincidence interval [CI] 1.04-1.52) and symptomatic non-AF recordings (OR 2.93, 95% CI 2.16-3.97). Pulse variability was not associated with reported symptoms. Conclusion: In persistent AF patients, simultaneous mobile app-based symptom and rhythm monitoring revealed a relatively low overall SRC, suggesting that the majority of patients experienced symptoms irrespective of AF. Extrasystoles can explain a minority of symptomatic non-AF PPG recordings. Pulse rate, but not pulse variability, is the main determinant of reported symptoms during AF and non-AF PPG recordings. Further studies are required to test whether mobile app-based SRC assessment can be implemented in current workflows and integrated into a personalized symptom and rhythm control AF management approach.